Self - assemblies of bolaamphiphilic molecules - Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad (Chemical Record, 2017)
The current buzzword in science and technology is self-assembly and molecular self-assembly is one of the most prominent fields as far as research in chemical and biological sciences is concerned. Generally, self-assembly of molecules occurs through weak non-covalent interactions like hydrogen bonding, π–π stacking, hydrophobic effects, etc. Inspired by many natural systems consisting of self-assembled structures, scientists have been trying to understand their formation and mimic such processes in the laboratory to create functional “smart” materials, which respond to temperature, light, pH, electromagnetic field, mechanical stress, and/or chemical stimuli. These responses are usually manifested as remarkable changes from the molecular (e. g., conformational state, hierarchical order) to the macroscopic level (e. g., shape, surface properties). Many molecules such as peptides, viruses, and surfactants are known to self-assemble into different structures. Among them, glycolipids are the new entries in the area of molecules that are being investigated for their self-assembly characteristics. Among the different classes of glycolipids like rhamnolipids and trehalose lipids, owing to their biological preparations and their structural novelty, sophorolipids (SLs) are evoking greater interest among researchers. Sophorolipids are a class of asymmetric bolas bearing COOH groups at one end and sophorose (dimeric glucose linked by an unusual β(1→2) linkage). The extreme membrane stability of Archaea, attributed to the membrane-spanning bolas (tetraether glycolipids), has inspired chemists to unravel the molecular designs that underpin the self-assembly of bolaamphiphilic molecules. Apart from these self-assembled structures, bolaamphiphiles find applications in many fields such as drug delivery, membrane mimicking, siRNA therapies, etc. The first part of this Personal Account presents some possible self-assembled structures of bolaamphiphiles and their mechanism of formation. The later part covers our work on one of the typical bolaamphiphiles known as sophorolipids.
Keywords: Bolaamphiphiles; gels; self-assembly; sophorolipids; vesicles